South Africa's Post-Apartheid Two-Step: Social Demands versus Macro Stability - Coulibaly, Brahima; Logan, Trevon D (American Economic Review, 2009)
South Africa's Post-apartheid Two-Step: Social Demands versus Macro Stability by Brahima Coulibaly and Trevon D. Logan. Published in volume 99, issue 2, pages 275-81 of American Economic Review, May 2009